(The Effect of pH, Mineral and Hydrocolloid addition on the Syneresis Index of Green Cincau (Premna Oblongifalia Merr.) Gel) - -, Djumarman; Arie Wardayanie, Ning Ima; D. Sirait, Shinta (Warta Industri Hasil Pertanian, 2005)
Â Research on the effect of pH,mineral and hydrolloid addition on the syneresis index of green cincau (Premna oblongifolia merr).Gel had been conducted.The objective of this research was to minimize get syneresis in order to prolong its stability so three will be a possibility of producing green cincau get in plastic cup.The result of this research indicated that get obtained by adding pectin could maintain its stability for one month an insignificant effect of syneresis and it had in natural taste.The more pectin added stronger was the gel texture but the taste turned to sour.Applying of 0.2% pectin produced green cincau gel having the best stability of one month strorage at room temperature without sour taste.